Features That Favor the Prediction of the Emplacement Location of Maar Volcanoes: A Case Study in the Central Andes, Northern Chile - Gabriel Ureta; Károly Németh; Felipe Aguilera; Rodrigo González (Geosciences, 2020)
Maar volcanoes are monogenetic landforms whose craters cut below the pre-eruptive surface and are surrounded by a tephra ring. Both the maar crater and the surrounding tephra rim deposits are typically formed due to magma–water explosive interactions. Northern Chile is located in the Central Volcanic Zone of the Andes where, in literature, 14 maars have been recognized as parasite (6) and individual (8) volcanoes. Amongst these individual maars, 3 of them, namely the Tilocálar Sur, Cerro Tujle, and Cerro Overo volcanoes, are not related to calderas and were emplaced <1 Ma ago by magmatic explosive-effusive and phreatomagmatic eruptions. Based on the evolution and control of the volcanic eruptive styles of these three maars, which have been determined in previous research through fieldwork, stratigraphic, morphometric, textural (density and vesicularity), petrographic, and geochemical analyses, a set of key features that favor a prediction of the emplacement location of maar volcanoes in Central Andes, northern Chile are proposed. The set of features that permit and favor the growth mechanisms for maar formations corresponds to (i) a compressive tectonic setting (e.g., ridge structures), (ii) groundwater recharge (e.g., snowmelt and seasonal rainfall), (iii) the lithological setting (e.g., layers of low permeability), (iv) the presence of aquifer and/or endorheic basins (e.g., lakes or salars), and (v) a period of stress relaxation that permits magma ascent to the surface in volcanically active areas. Considering these characteristics, it is possible to identify places where phreatomagmatic eruption can occur. If the magma ascent flux is lower than the groundwater flux, this can lead to a phreatomagmatic eruption because of groundwater coming into contact with the magma. These eruptive features evidence internal—and external—factors that play an essential role in the transition from explosive-effusive magmatic to phreatomagmatic volcanic eruption styles during the same eruptive period that is one of the biggest challenges in volcanic hazard evaluations. Although, in this contribution, a set of features that permit and favor the growth mechanisms for a prediction of the emplacement location of maars in northern Chile is proposed, these considerations could also be applied to identify potential locations in other parts of the world where magma–water interaction eruption could occur. Therefore, this approach could be useful in the prediction of hydromagmatic volcanic eruptions and, thus, in mitigating the impact of volcanic hazard for the inhabitants of the surrounding areas.